Theological Reflection on the Ecological Problem in Relation to the Accra Confession: An East Asian Perspective1. (7th October 2013) - Lam, Jason
Abstract Compared with the declarations related to ecological concerns produced by other ecclesial bodies, the Accra Confession is not a latecomer.2 But in view of the increasingly severe situation the world is now facing (for example, the nuclear threat, from Chernobyl to Three Mile Island and, recently, Fukushima), it seems that the "prophetic" voice from the Christian church always comes too late. Be that as it may, every Christian should share the common mission of being a peacemaker with all of God's creation, despite the groaning of the earth in face of all sorts of threat and injustice. In this paper, I first review the Accra Confession in relation to ecological concerns. Then, as it seems to me that the interfaith perspective has received less attention, I develop a theological reflection based on my East Asian cultural resources in order to make a contribution to the global problem from a regional stance. Finally I provide some practical suggestions.